Synthesis of ZnO/Fe3O4 as a composite catalyst using hydrothermal method for sono catalytic degradation of phenol in pome / Abdul Hadi Abdul Rahim - Abdul Rahim, Abdul Hadi (2017)
The present study has synthesized composite ZnO/Fe3O4 using hydrothermal technique at temperature of 170oC in order to be used as a sonocatalyst. The VSM and FTIR have been applied to characterize the magnetization and chemical properties of the composite ZnO/Fe3O4. Based on the observations, the prepared composite ZnO/Fe3O4 has low saturation magnetization (8.66 emu/g) and low coercivity (20.85 Oe). The ZnO/Fe3O4 was successfully prepared in this study. Moreover, the experimental of sonocatalytic degradation has been fully examined by using a ultrasonic bath with 50 kHz in frequency. The result demonstrates a relatively low catalytic degradation efficiency of the phenol solution which was only 22 %.